Seventy years of bariatric surgery: A systematic mapping review of randomized controlled trials. (17th January 2022) - Rives‐Lange, Claire; Rassy, Nathalie; Carette, Claire; Phan, Aurelie; Barsamian, Charles; Thereaux, Jeremie; Moszkowicz, David; Poghosyan, Tigran; Czernichow, Sebastien
Summary: While research publications on bariatric surgery (BS) have grown significantly over the past decade, there is no mapping of the existing body of evidence on this field of research. We performed a systematic review followed by a mapping of randomized controlled trials (RCTs) in BS for people with obesity. From January 2020 to December 2020, we performed a systematic review of RCTs evaluating BS, versus another surgical procedure, or versus a medical control group, through a search of Embase and PubMed. There was no restriction on outcomes for study selection. A total of 114 RCTs were included, most (73.7%) of which were based on a comparison with Roux‐en‐Y gastric bypass (RYGB) and conducted between 2010 and 2020. Only 15% of the trials were multicenter and few (3.5%) were international. The median number of patients enrolled was 61 (interquartile range [IQR]: 47.3–100). Follow‐up time was 1 to 2 years in 36% and 22.8% of the trials, respectively. Weight loss was the most studied criterion (87% of RCTs), followed by obesity‐related diseases, and medical and surgical complications (73%, 54%, and 47% of RCTs, respectively). Nutritional deficiency frequency, body composition, and mental health were little studied (20%, 18% and 5% of RCTs, respectively). Our literature review revealed that much research in BS is wasted because of replication of RCTs on subjects for which there is already body of evidence, with small populations and follow‐up times mostly below 2 years. Yet several research questions remain unaddressed, and there are few long‐term trials. Future studies should take into account the experience of the past 70 years of research in this field.